2018
DOI: 10.1101/401661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aurora A inhibition limits centrosome clustering and promotes mitotic catastrophe in cells with supernumerary centrosomes

Abstract: The presence of supernumerary centrosomes is prevalent in cancer, where they promote the formation of transient multipolar mitotic spindles. Active clustering of supernumerary centrosomes enables the formation of a functional bipolar spindle that is competent to complete a bipolar division. Disruption of spindle pole clustering in cancer cells promotes multipolar division and generation of non-proliferative daughter cells with compromised viability. Hence molecular pathways required for spindle pole clustering… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Centrosome clustering is a dynamic process that can take an hour or longer to achieve (Kwon et al, 2008; Navarro-Serer et al, 2019) and analysis of a single time point in mitosis cannot distinguish between a delay versus a deficit in centrosome clustering. To further assess the observed increase in multipolar spindles seen following cortical dynein disruption, cells were additionally treated with the protease inhibitor MG132 prior to assessment of centrosome positioning and spindle structure.…”
Section: Resultsmentioning
confidence: 99%
“…Centrosome clustering is a dynamic process that can take an hour or longer to achieve (Kwon et al, 2008; Navarro-Serer et al, 2019) and analysis of a single time point in mitosis cannot distinguish between a delay versus a deficit in centrosome clustering. To further assess the observed increase in multipolar spindles seen following cortical dynein disruption, cells were additionally treated with the protease inhibitor MG132 prior to assessment of centrosome positioning and spindle structure.…”
Section: Resultsmentioning
confidence: 99%
“…2). 101 In their study, AURKA inhibition promoted a panel of AML cells with extra centrosomes to produce multipolar and disorganized spindles, reducing the proliferation and viability of daughter cells. 101 Various transcription factors regulating AURKA have been identified.…”
Section: Aurka-associated Centrosome Defects and Extra Centrosome Clu...mentioning
confidence: 99%
“…101 In their study, AURKA inhibition promoted a panel of AML cells with extra centrosomes to produce multipolar and disorganized spindles, reducing the proliferation and viability of daughter cells. 101 Various transcription factors regulating AURKA have been identified. Examples include E4TF1, one of the E26 transformation-specific (ETS) family proteins, which can positively regulate AURKA transcriptional levels, 102 and alterations among ETS gene expression are often detected in various hematological malignancies including lymphoma and leukemia.…”
Section: Aurka-associated Centrosome Defects and Extra Centrosome Clu...mentioning
confidence: 99%
“…Although centrosome amplification is a common characteristic of solid and hematological cancers, cancer cells tend to cluster supernumerary centrosomes into two group to enable a bipolar mitosis [Kwon et al 2008]. Recently, it has shown that Aurora-A inhibition limits centrosome clustering and promotes mitotic multipolarity in cells with supernumerary centrosomes [Navarro-Serer et al 2018]. With these in mind, it is therefore tempting to speculate that multipolar spindle and multinucleation induced by geraniin in HCT116 cells may be the combined consequences of centrosome overduplication and declustering resulting from reduced expression of Plk-4, Plk-1, and Aurora-A.…”
Section: Disscussionmentioning
confidence: 99%